2009
DOI: 10.4269/ajtmh.2009.81.195
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and Environmental Risk Factors for American Cutaneous Leishmaniasis (ACL) in the State of Alagoas, Brazil

Abstract: The multiplicity of factors involved in the transmission of the American cutaneous leishmaniasis (ACL) constitutes a challenge to its control. Thus, knowledge of such factors may contribute extremely toward redefining the control strategies. The aim of this study was to identify sociodemographic and environmental factors relating to ACL transmission in the State of Alagoas, Brazil. A case-control study with incident cases was conducted. Diagnostic criteria were the presence of compatible skin lesions, laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 11 publications
2
21
0
Order By: Relevance
“…Our results corroborate those of other authors, who observed percentages of 39.8% to 56.7% for the same age group 7 , 10 , 11 . ACL is more important in the age group of economically active adults in comparison with visceral leishmaniasis, which affects higher percentages of children 12 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results corroborate those of other authors, who observed percentages of 39.8% to 56.7% for the same age group 7 , 10 , 11 . ACL is more important in the age group of economically active adults in comparison with visceral leishmaniasis, which affects higher percentages of children 12 .…”
Section: Discussionsupporting
confidence: 92%
“…This was a significant feature of our study in this municipality. Theoretically, this working environment is closer to sandfly habitats, which would therefore increase their chances of becoming infected 7 . …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations